Pengaruh Brand Ambassador, Labelisasi Halal, dan Harga terhadap Keputusan Pembelian Produk Skincare Wardah pada Generasi Z di Kota Medan - Maya Almalia Azhari; Alim Murtani (Lembaga Yasin AlSys, 2025)
The purchasing decision is a critical phase in consumer behavior, encompassing the selection, acquisition, and use of products to fulfill individual needs and desires. This study aims to analyze the influence of brand ambassador, halal labeling, and price on the purchasing decisions of Wardah skincare products among Generation Z in Medan City. A quantitative method with a causal associative approach was employed, utilizing cross-sectional primary data collected through questionnaires. The study population comprised Generation Z individuals in Medan who have purchased and used Wardah skincare products, with a sample of 156 respondents selected through random sampling. The analysis revealed that, partially, the variables brand ambassador (t = 5.323; p < 0.05), halal label (t = 5.316; p < 0.05), and price (t = 7.224; p < 0.05) each have a significant effect on purchasing decisions. Furthermore, the simultaneous test results (F = 139.810; p < 0.05) indicate that these three variables collectively exert a significant influence on purchasing decisions. These findings underscore the importance of marketing strategies involving public figures, consumer trust in halal certification, and price appeal in shaping the purchasing behavior of young consumers, particularly Generation Z as a potential market segment.